2001
DOI: 10.1002/ijc.1201
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibition of human mammary carcinoma by liposomal hexadecylphosphocholine: Participation of activated macrophages in the antitumor mechanism

Abstract: This study was undertaken to investigate the antitumor effect of liposomal hexadecylphosphocholine (L-HPC), a synthetic phospholipid encapsulated into multilamellar vesicles (MLV). The effect of these liposomes was tested in an orthotopic nude mouse model using the human mammary carcinomas MDA-MB 435 and 231. The main interest of the investigation was to study whether activated macrophages are substantially involved in the tumor growth inhibition mechanism. The growth of both MDA-MB 435 and 231 tumors in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Several groups have proposed using macrophages to target drug delivery, and whether this strategy will be effective remains to be determined 6, 90, 95, 165, 166…”
Section: Future Directionsmentioning
confidence: 99%
“…Several groups have proposed using macrophages to target drug delivery, and whether this strategy will be effective remains to be determined 6, 90, 95, 165, 166…”
Section: Future Directionsmentioning
confidence: 99%
“…These effects were demonstrated in rat liver Kupffer cells [89], the human histiocytic line U937 [90] and in peritoneal macrophages harvested from mice that had been treated with HePC-containing liposomes in vivo [91]. The role of mediators released by activated macrophages in the antitumor mechanism of HePC was investigated by Eue [92] using a human mammary carcinoma growing in nude mice. In this study, the most important macrophage products were found to be TNF and interleukin-6.…”
Section: Incorporation Of Hepc Into Liposomesmentioning
confidence: 99%
“…The severe lytic side effects against red blood cells have prohibited intravenous administration of sufficiently high therapeutic concentrations of the AELs. To circumvent the hemolytic effect, various preclinical formulation and administration strategies have been developed including oral and intraperitoneal administration as well as the development of liposomes incorporated with a low amount of the AELs [65,66]. In the clinic, a particular anticancer lipid named hexadecylphosphocholine, has successfully been used in topical treatment of cutaneous breast cancer metastases [67].…”
Section: Liposomes Made Of Prodrug Anticancer Etherlipidsmentioning
confidence: 99%